FACTORS ASSOCIATED WITH ANXIETY IN OLDER ADULTS AT THE NATIONAL GERIATRIC HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Background: Anxiety disorders are common in the elderly, significantly impacting their quality of life and increasing the disease burden.Objectives: To investigate some factors related to anxiety in elderly inpatients at the National Geriatric Hospital.Method: A descriptive, cross-sectional study was conducted involving 255 inpatients aged 60 years and older, receiving treatment at the Mental Health Department of the National Geriatric Hospital from August 2022 to December 2022. Patients were interviewed directly to gather comprehensive information on their anxiety status using the Hamilton Anxiety Rating Scale (HAM-A) and the characteristics of factors associated with this anxietyResults: Our study results showed that several factors were associated with anxiety in the elderly, such as female gender (OR=2.07, 95%CI=1.206-3.554, p=0.008), education level below high school (OR=1.99, 95%CI=1.19-3.33, p=0.008), difficult or average economic conditions (OR=1.86, 95%CI=1.50-3.44, p=0.046), and psychological trauma (OR=3.71, 95%CI=1.92-7.20, p
Keywords: anxiety, elderly, associated factors